The Anxiety-Provoking Risks of Performance Management and Its Alternative Solutions in the Banking Environment - Santenac, Rene (Journal of Applied Business and Economics, 2021)
The theory of performance has a unique character as it has allowed the creation of large organizations. It borrows from economic theory the criteria of effectiveness and efficiency. Performance theory itself has a sound foundation, particularly, financial and accounting ones without taking into account its global field of investigation: the organization and the man. In other words, this part of psychology acts and interacts with the organization. This article pursues four main objectives. First, it reminds the central elements of the theory of performance regarding the “capabilities” of “stakeholders.” Second, it aims to identify the factors of performance failure caused by a lack of consideration of global criteria to build a coherent model of optimal management. Third, it maps the risks caused by defects, differences, and gaps in performance management. Finally, it tries to provide an alternative plausible solution to establish more effective performance management. The primary domain is management science while the input from psychology remains limited and applicable only to specific elements such as psycho-social phenomena.